2014
DOI: 10.1371/journal.pone.0087817
|View full text |Cite
|
Sign up to set email alerts
|

Application of BMD Approach to Identify Thresholds of Cadmium-Induced Renal Effect among 35 to 55 Year-Old Women in Two Cadmium Polluted Counties in China

Abstract: BackgroundCadmium (Cd) is a heavy metal that can cause renal tubular dysfunction in humans. Women are among the high-risk group for Cd health effects. Determining the thresholds of Cd-induced renal effects is important. Thus, in this article, we aimed to identify the benchmark dose (BMD) and its low limit (BMDL) levels as the Cd thresholds for Chinese women.MethodsEpidemiologic investigation was performed in county A and county B to obtain data on Cd exposure and its renal effect on respondents. Levels of Cd (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…However, there is still a lack of information on the reference level of Cd exposure for the adverse health effects in the general Chinese population. The limited studies on the Chinese population used a much smaller sample size than the sample sizes of the Japanese population reported in other studies (374 to 790 participants vs. 1270 to 3103 participants) [ 14 17 , 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is still a lack of information on the reference level of Cd exposure for the adverse health effects in the general Chinese population. The limited studies on the Chinese population used a much smaller sample size than the sample sizes of the Japanese population reported in other studies (374 to 790 participants vs. 1270 to 3103 participants) [ 14 17 , 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese population data from previous studies suggested that the benchmark dose lower confidence limit (BMDL) of UCd for renal effects ranged from 2.5 μg/g cr to 10.3 μg/g cr in males and 1.4 μg/g cr to 11.4 μg/g cr in females [ 13 16 ]. Another study reported that the BMDLs of UCd were between 0.5 μg/g cr to 1.2 μg/g cr in a Swedish population [ 17 ], whereas some other researchers reported BMDLs ranging from 0.44 μg/g cr to 12.18 μg/g cr in Chinese populations [ 18 21 ]. The BMDL values may have been significantly affected by many factors, such as the sample population and Cd exposure levels, thereby necessitating further studies to identify the possible factors affecting the BMD evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…This value is higher than that in studies . Another study conducted in two Cd-polluted areas in south and central China showed that the BMD/BMDL values of U-Cd for 35-55-year-old women were 1.07/0.44 and 2.12/ 0.53 μg/g Cr based on β 2 -MG and NAG, respectively, at a 90% cutoff value and 5% BMR (Qi et al, 2014). These values are similar to those of a study conducted in Cd non-polluted areas in southeast China, with BMD 05 /BMDL 05 and BMD 10 /BMDL 10 values of U-Cd for RBP, β 2 -MG and NAG of women ranged from 1.35/0.64 to 1.70/0.76 μg/g Cr and 2.10/1.34 to 2.43/1.53 μg/g Cr, respectively, at a 90% cut-off value (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Residents in these Cd-polluted areas are at risk of renal effects due to long-term exposure to Cd. However, only a few studies (Hong, Jin, & Zhang, 2004;Hu et al, 2014;Jin et al, 2004;Qi et al, 2014) have investigated the body burden of Cd and renal dysfunction effects and utilized BMD to estimate the threshold levels of U-Cd or B-Cd for residents in these polluted areas in China until now.…”
mentioning
confidence: 99%
“…those with U-Cd of <2.00 µg/g cr) was chosen, and the BMD approach was adopted by combining both sets of data from CA and CB subjects, to present either LogProbit or LogLogistic Models according to the AIC values. The U-Cd levels were divided into intervals of <2.00 µg/g cr, 2.01–4.00 µg/g cr, 4.01–10.00 µg/g cr, and >10.00 µg/g cr [47] . The findings of both reports are similar to those of Suwazono et al and Jin et al [13] , [46] .…”
Section: Discussionmentioning
confidence: 99%